Vitamin D deficiency in critically ill COVID-19 ARDS patients. Issue 12 (December 2022) - Notz, Quirin; Herrmann, Johannes; Schlesinger, Tobias; Kranke, Peter; Sitter, Magdalena; Helmer, Philipp; Stumpner, Jan; Roeder, Daniel; Amrein, Karin; Stoppe, Christian; Lotz, Christopher; Meybohm, Patrick
Summary: Background & aims: Vitamin D's pleiotropic effects include immune modulation, and its supplementation has been shown to prevent respiratory tract infections. The effectivity of vitamin D as a therapeutic intervention in critical illness remains less defined. The current study analyzed clinical and immunologic effects of vitamin D levels in patients suffering from coronavirus disease 2019 (COVID-19) induced acute respiratory distress syndrome (ARDS). Methods: This was a single-center retrospective study in patients receiving intensive care with a confirmed SARS-CoV-2 infection and COVID-19 ARDS. 25-hydroxyvitamin D and 1, 25-dihydroxyvitamin D serum levels, pro- and anti-inflammatory cytokines and immune cell subsets were measured on admission as well as after 10–15 days. Clinical parameters were extracted from the patient data management system. Standard operating procedures included the daily administration of vitamin D3 via enteral feeding. Results: A total of 39 patients with COVID-19 ARDS were eligible, of which 26 were included in this study as data on vitamin D status was available. 96% suffered from severe COVID-19 ARDS. All patients without prior vitamin D supplementation (n = 22) had deficient serum levels of 25-hydroxyvitamin D. Vitamin D supplementation resulted in higher serum levels of 25-hydroxyvitamin D but not did not increase 1, 25-dihydroxyvitamin D levels after 10–15 days. Clinical parameters did not differ between patients with sufficient or deficient levels of 25-hydroxyvitamin D. Only circulating plasmablasts were higher in patients with 25-hydroxyvitamin D levels ≥30 ng/ml (p = 0.029). Patients with 1, 25-dihydroxyvitamin D levels below 20 pg/ml required longer mechanical ventilation (p = 0.045) and had a worse acute physiology and chronic health evaluation (APACHE) II score (p = 0.048). Conclusion: The vast majority of COVID-19 ARDS patients had vitamin D deficiency. 25-hydroxyvitamin D status was not related to changes in clinical course, whereas low levels of 1, 25-dihydroxyvitamin D were associated with prolonged mechanical ventilation and a worse APACHE II score.